Metagenomic analysis of the begomovirus diversity in tomatoes in Central Brazil and impact of the Ty-1 tolerance gene on viral evolutionary dynamics. - REIS, L. de N. A. dos (2020)
The general objective of the present work was to conduct metagenomics studies on the diversity of begomoviruses in tomatoes in Brazil. The specific objectives were: (a) to carry out comparative studies of the begomovirus diversity infecting tomato plants with and without the Ty?1 gene and (b) to catalog the predominant viral species and/or new begomoviruses occurring in tomato plants with and without the Ty?1 gene. For this, 107 samples were collected in production fields in Goiás (n = 56), Distrito Federal (n = 27) and Minas Gerais (n = 24) between the years 2002 and 2016. The total DNA of the samples was extracted and submitted to PCR using primers to detect begomovirus and also with primers for the genomic region linked to the Ty?1 gene. Subsequently, the samples were subjected to enrichment via RCA (Rolling Circle Amplification) and divided into two pools: tomatoes without the Ty?1 gene (n = 64) and with the Ty?1 gene (n = 43). The two pools were sequenced on an Illumina HiSeq 2500 platform. The obtained sequences were assembled using the CLC Genomics Workbench 11.0 program and analyzed in Geneious 10.1. The sequences were then compared to viral sequences present on GenBank using the BLASTn algorithm.